The relevance of physical forces on land-use change and planning process. Issue 4 (2nd April 2016) - Pato, Rosinda Leonor; Castro, Paula; Tavares, Alexandre O.
Abstract : This study analysed the importance of physical forces on land-use change, on the planning framework in a Portuguese periurban area. A temporal matrix showing the trajectories of land transformation was obtained. A multivariate redundancy analysis explored the importance of physical parameters on temporal and spatial land-use change. A content analysis on urban or municipal master plans was made framing the importance of physical parameters on the planning process. The results highlighted a consistent trajectory of profound land-use changes with distinctive trajectories, with increasingly complex patterns with a limited dependence on physical variables. The trajectories were more related to the planning framework, where political actors and planning managers seemed to be most important. A theoretical model balancing three main components – physical forces, actors, and land transformation (DFA-C model) is proposed, reflecting the informal relationships between physical parameters and actors during the planning process.